Recognising choice : a study of the changing politics of the common agricultural policy through an analysis of the MacSharry reform debate in Ireland and the Netherlands - Vihinen, Hilkka (Julkaisuja / MTT Taloustutkimus, ISSN 1458-2996, 2001)
Abstract.
Keywords: Euroopan unioni : maatalouspolitiikka; Euroopan unioni : lantbrukspolitik; maatalouspolitiikka; EU-maat; maatalous; jordbrukspolitik; EU-länder; lantbruk